Urinary concentrations of phenols and phthalate metabolites reflect extracellular vesicle microRNA expression in follicular fluid. (February 2019) - Martinez, Rosie M.; Hauser, Russ; Liang, Liming; Mansur, Abdallah; Adir, Michal; Dioni, Laura; Racowsky, Catherine; Bollati, Valentina; Baccarelli, Andrea A.; Machtinger, Ronit
Abstract: Background: Phenols and phthalates are potential endocrine disrupting chemicals (EDCs) that are associated with adverse health outcomes. These EDCs dysregulate a number of biomolecules and pathways, including microRNAs. MicroRNAs can be carried in transport systems called extracellular vesicles (EVs) that are present in most biofluids. EVs in the follicular fluid, which fills the ovarian follicle and influences oocyte developmental competency, carry microRNAs (EV-miRNAs) that have been associated with In Vitro Fertilization (IVF) outcomes. However, it remains unclear whether EDCs affect EV-miRNAs in follicular fluid. Objectives: This study sought to determine whether urinary concentrations of phenols and phthalates biomarkers are associated with EV-miRNAs expression in follicular fluid collected from women undergoing IVF treatment. Methods: This cross-sectional study included 130 women recruited between January 2014 and August 2016 in a tertiary university-affiliated hospital. Participants provided urine samples during ovarian stimulation and on the day of oocyte retrieval. We assessed urinary concentrations of five phenols, eight phthalate metabolites, and one phthalate alternative metabolite. EV-miRNAs were isolated from follicular fluid and their expression profiles were measured using the TaqMan Open Array® Human microRNA panel. We fitted multivariable linear regression models and principal component analysis to examine associations between individual and molar sums of exposure biomarkers and EV-miRNAs. Results: Of 754 miRNAs tested, we detected 133 EV-miRNAs in the microRNA array which expressed in at least 50% of the follicular fluid samples. After adjusting for multiple testing, we identified eight EV-miRNAs associated with individual phenols and phthalate metabolites, as well as molar ΣDEHP that met a q < 0.10 false-discovery rate (FDR) threshold. Hsa-miR-125b, hsa-miR-106b, hsa-miR-374a, and hsa-miR15b was associated with mono(2-ethylhexyl) phthalate concentrations, hsa - let - 7c with concentrations mono-2-ethyl-5-hydroxyhexyl phthalate (MEHHP), mono-2-ethyl-5-oxohexyl phthalate (MEOHP), mono-2-ethyl-5-carboxypentyl phthalate (MECPP), and the sum of metabolites of di(2-ethylhexyl) phthalate, hsa-miR-24 with mono-n-butyl phthalate concentrations, hsa-miR-19a with cyclohexane-1, 2-dicarboxylic acid monohydroxy isononyl ester (MHiNCH), and hsa-miR-375 with ethyl paraben concentrations. Using Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, gene targets and pathways of these EV-miRNAs were predicted in silico and 17 KEGG FDR-significant pathways related to follicular development and oocyte competence were identified. Conclusions: Our results show that urinary concentrations of select phenol and phthalate metabolites are correlated with altered EV-miRNAs expression in follicular fluid. These findings may provide insight regarding the molecular mechanisms underlying adverse effects of phenol and phthalate exposure on female fertility. Highlights: Women are exposed to phthalate and phenols before conception. Exposure to phenols and phthalates are correlated with expression of EV-miRNAs in follilcular fluid. Gene targets and pathways of these EV-miRNAs are related to follicular development and oocyte competence.